IDENTIFIKASI PEMELIHARAAN SALURAN SEKUNDER (SPD) DAERAH IRIGASI RAWA DELTA AIR SUGIHAN KANAN DI DESA SUKA MULYA - Ade Agung Santoso; Firdaus Firdaus (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
Periodic maintenance of irrigation channels represents a fundamental aspect in maintaining agricultural system sustainability, particularly in swamp irrigation areas that possess unique characteristics and specific challenges. This study examines the implementation of periodic maintenance on secondary channels of Sugihan Kanan Swamp Irrigation Area in Suka Mulya Village, executed through the Public Works and Public Housing Department. The implementation methodology encompasses equipment and workforce mobilization, channel measurement using GPS technology and precision measuring instruments, and application of occupational safety and health management systems (SMK3). Comprehensive field survey stages include preparation, site inspection, and visual documentation to obtain accurate data on existing channel conditions. Main construction work comprising soil excavation and embankment refinement was executed using excavators with gradual techniques to achieve optimal channel profiles. Detailed drawing planning using AutoCAD software with 1:1000 scale ensures accurate visualization and facilitates field implementation. Implementation results demonstrate that systematic and structured approaches in irrigation channel maintenance can enhance water distribution effectiveness, prevent infrastructure damage, and support agricultural productivity. Effective coordination between technical teams and local communities serves as the key to sustainable maintenance project success. Keywords: periodic maintenance, irrigation channels, swamp irrigation area, occupational safety management system, agricultural productivity